ANALISIS PENDUKUNG KEBERHASILAN SEBUAH E- DALAM MEMBANGUN USAHA BISNIS ONLINE: PERSEPSI KONSUMEN - Nunu Kustian (Universitas Indraprasta PGRI, 2015)
Growth of E-Commerce difficult for consumers to determine the commercial activities online. The aim was to determine the level of priority, knowing the result of the weighting of criteria and sub-criteria which further concludes priority analysis supporting the success of an E-Commerce perceptions of consumers as users of online shopping. Selection is done by interpreting consumer perception. Each interpretation will be evaluated and processed by pairwise comparison using AHP. Criteria for success factors supporting E-Commerce and the best alternative produced by this method compared with Expert Choice software. The interpretation of consumer perceptions obtained the highest weighted criteria that Trust In Store 0.327 or equal to 3.27% and the site Lazada as the best alternative to the weight of 0.421. This shows that the better the perception of the consumer, the higher the success rate E-Commerce in building an online business venture. Keywords : Consumer Perception, Analytical Hierarchy Process, Matriks Pairwise Comparison, Expert Choice